Challenges faced by female councillors in Ekurhuleni Metropolitan Municipality - Marumo, Deborah (My University, 2015)
This paper investigates the challenges facing female councillors in Ekurhuleni Metropolitan Municipality. It is based on the assumption that female councillors are still faced with numerous challenges despite all efforts to address that problem. The factors that discourage participation of women in politics are classified as ideological factors, political factors, socio-cultural factors, economic factors and media. It becomes very important for Ekurhuleni Metropolitan Municipality to understand that these challenges exist so that proper and relevant interventions may be developed, to assist in addressing those challenges. Gender mainstreaming is discussed, which explains a variety of tools and instruments used at international, regional and local levels. These tools are meant to address gender equality: Millennium Development Goals (MDGs), Elimination of All Forms of Discrimination against Women (CEDAW), Beijing Declaration and Platform for Action (BPA), Constitution of the Republic of South Africa, Municipal Structural Act and Municipal Systems Act. A qualitative study was used to respond to the research questions that focused on challenges faced by female councillors, support structures available for female councillors and the effectiveness of these support structures. The focus is on feminist social research. The assumption is that men and women have different perceptions of life because of their social status. The findings of the research are that society is still divided along gender roles. Women are considered as the main care givers for the family. Women are not part of political inner circles, where major political decisions are taken, including deployment to key and strategic positions. Socially, women are still facing challenges of low education levels that result in a lack of communication skills, which in turn hampers their ability to lead effectively. In terms of economy, most women are in low income paying jobs. This makes it difficult for women to campaign for strategic decision-making positions, as campaigning involves the use of money. Women leaders are also not using media effectively to market themselves. iii There is laxity in terms of implementation of gender equity policies. Support structures and system exist solely on paper. There is no proper assessment to check if systems implemented to support women are effective and relevant.
Thesis (M.M. (Public and Development Management))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Public and Development Management, 2014.